Embracing Uncertainty During the Crisis - Maria Alina Carataș; Elena Cerasela Spătariu; Raluca Andreea Trandafir (Ovidius University Annals: Economic Sciences Series, 2020)
The purpose of this paper is to emphasize the impact of uncertainty over the economic environment in the current crisis installed within the COVID-19 pandemic that is unprecedented because there has never been a phenomenon of such magnitude, a global crisis, with a profound, extensive and more complex impact than any other event that decision-makers have considered so far. The current pandemic caused an uncertainty shock globally, which rose into recession. There is uncertainty about the consequences of the crisis and impact on global health, how the world will live and work, how relations between the largest states will be influenced, how the roles of states in trade relations will change, considering the responses to the crisis.